Code of practice for in-service inspection and testing of electrical equipment. (Institution of electrical engineers, 2001)
This manual offers a code of practice for the in-service inspection and testing of electrical equipment. It includes advice on compliance with health and safety legislation. The text specifies the frequency and scope of inspections and testing in different environments.